(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God who enlightened the minds of His pious servants with the light of His clear Book and made the Qur’an a guidance and mercy for the worlds, and prayers and peace be upon the Seal of the Prophets and Messengers Muhammad (may God bless him and grant him peace) and his family and companions altogether.As for afterI divided the research into an introduction in which I knew the truth about misdemeanor and what it includes of meanings, and I mentioned the sayings of the interpreters about the meaning of misdemeanor, and I mentioned some opinions about the meaning of misdemeanor in the figurative sense. As for the second topic, I took an example of the first meaning of misdemeanor. The most important results that I reached in the research, this is my research, in which I do not claim perfection. Perfection belongs to God, Glory be to Him, and I have put in it as much effort and hardship as I can.